Lexical Specificity Training Effects in Second Language Learners. Issue 2 (June 2015) - Janssen, Caressa; Segers, Eliane; McQueen, James M.; Verhoeven, Ludo
<x xml:space="preserve">Abstract</x> Children who start formal education in a second language may experience slower vocabulary growth in that language and subsequently experience disadvantages in literacy acquisition. The current study asked whether lexical specificity training can stimulate bilingual children's phonological awareness, which is considered to be a precursor to literacy. Therefore, Dutch monolingual and Turkish‐Dutch bilingual children were taught new Dutch words with only minimal acoustic‐phonetic differences. As a result of this training, the monolingual and the bilingual children improved on phoneme blending, which can be seen as an early aspect of phonological awareness. During training, the bilingual children caught up with the monolingual children on words with phonological overlap between their first language Turkish and their second language Dutch. It is concluded that learning minimal pair words fosters phoneme awareness, in both first and second language preliterate children, and that for second language learners phonological overlap between the two languages positively affects training outcomes, likely due to linguistic transfer.